Effects of retaining different number of mother bamboo on the growth and NSCs allocation of new-born seedlings in Phyllostachys edulis at different age - Binao Zhou; Xu Zhang; Hanjiao Zhang; Wenjing Yao; Long Li; Shuyan Lin; Fuliang Cao (BMC Plant Biology)
Abstract Background Non-structural carbohydrates (NSCs) are key substances for metabolic processes in plants, providing energy for growth, development, and responses to environmental stress. Pruning mother bamboo in a clump can significantly affect the NSCs allocation of new shoots, thereby affecting their growth. Moso bamboo (Phyllostachys edulis) is an important economic bamboo species with a highest planting area in China. However, it remains unclear how many mother bamboo left maximize the influence in moso bamboo seedlings at different age. Results This study investigated the effects of retaining different number of mother bamboo on the morphological characterization and NSCs allocation of new-born seedlings in moso bamboo at two-year-old and three-year-old, respectively. Retaining more mother bamboo significantly promoted the plant height and diameter of new shoots, particularly in the two-year-old clumps. The growth rate of new shoots increased with the number of mother bamboo in the two-year-old clumps, while it remained relatively stable in the three-year-old clumps. The allocation strategy of NSCs also showed significant differences when retaining different number of mother bamboo across growth stages. NSCs content continuously increased with the growth of new shoots during the rapid growth phase, which reached peak in all parts at the end of the rhizome elongation stage. In two-year-old bamboo seedlings, the NSCs content increased with the number of retained mother plants. Significant differences were found between different treatments, particularly between those with one and four mother bamboos left. It was similar in the three-year-old clumps. However, there were no significant differences in NSCs content among the treatments. Conclusion Reducing the number of mother bamboo appropriately can promote the growth of new shoots in moso bamboo. The two-year-old clumps were more dependent on the number of mother bamboo, while it was less pronounced for three-year-old clumps. In production practice, it is recommended that three mother bamboos are retained for two-year-old clumps and two to three mother bamboos for three-year-old clumps. This approach can expand the afforestation area while ensuring the survival rate of new seedlings in moso bamboo.